Redescoberta de Mackenziaena severa (Lichtenstein, 1823) (Aves: Thamnophilidae) no limite sul de sua distribuição geográfica, Rio Grande do Sul, Brasil (Lundiana: International Journal of Biodiversity, 2011)
In this short note I present records of the Tufted Antshrike, Mackenziaena severa (Lichtenstein, 1823), in a forest fragment located between the municipalities of Campo Bom and Dois Irmãos (29º37’S, 51º03’W), state of Rio Grande do Sul, southern Brazil, close to its previous historical southernmost record (Igrejinha, around 1880). Recent records known for the species in the state (second half of the 20th century) are all from 300 km northwestward. I suggest that the specimens recorded here are part of a small relictual population and do not represent an event of recent re-colonization from other areas.